2015
DOI: 10.1515/pjct-2015-0060
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption Performance of Biodegradable Polymer Powders for the Removal of Gallium(III) ions from Aqueous Solution

Abstract: Gallium (Ga) is considered an important element in the semiconducting industry and as the lifespan of electronic products decrease annually Ga-containing effl uent has been increasing. The present study investigated the use of biodegradable polymer powders, crab shell and chitosan, in the removal of Ga(III) ions from aqueous solution. Ga(III) biosorption was modeled to Lagergren-fi rst, pseudo-second order and the Weber-Morris models. Equilibrium data was modeled to the Langmuir, Freundlich and Langmuir-Freund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 38 publications
3
2
0
Order By: Relevance
“…T 2.5 as the optimal value was used for the subsequent adsorption experiments. A study on the effects of pH on gallium adsorption (Figure 8) revealed that pH 2.5 was optimal for maximum Ga adsorption efficiency, which was in agreement with the literature [3,20,51]. A lower pH introduces competition from greater concentrations of H + ions with gallium ions, thus preventing adsorption of the Ga 3+ cations [20,51].…”
Section: Effect Of Phsupporting
confidence: 85%
See 4 more Smart Citations
“…T 2.5 as the optimal value was used for the subsequent adsorption experiments. A study on the effects of pH on gallium adsorption (Figure 8) revealed that pH 2.5 was optimal for maximum Ga adsorption efficiency, which was in agreement with the literature [3,20,51]. A lower pH introduces competition from greater concentrations of H + ions with gallium ions, thus preventing adsorption of the Ga 3+ cations [20,51].…”
Section: Effect Of Phsupporting
confidence: 85%
“…A study on the effects of pH on gallium adsorption (Figure 8) revealed that pH 2.5 was optimal for maximum Ga adsorption efficiency, which was in agreement with the literature [3,20,51]. A lower pH introduces competition from greater concentrations of H + ions with gallium ions, thus preventing adsorption of the Ga 3+ cations [20,51].…”
Section: Adsorption Kinetics: Model Selection and Fittingsupporting
confidence: 85%
See 3 more Smart Citations